IMA genome - F14 - Magriet A. van der Nest; Renato Chávez; Lieschen De Vos; Tuan A. Duong; Carlos Gil-Durán; Maria Alves Ferreira; Frances A. Lane; Gloria Levicán; Quentin C. Santana; Emma T. Steenkamp; Hiroyuki Suzuki; Mario Tello; et al. (IMA Fungus)
Abstract Draft genomes of Penicillium roqueforti, Fusarium sororula, Chalaropsis populi, and Chrysoporthe puriensis are presented. Penicillium roqueforti is a model fungus for genetics, physiological and metabolic studies, as well as for biotechnological applications. Fusarium sororula and Chrysoporthe puriensis are important tree pathogens, and Chalaropsis populi is a soil-borne root-pathogen. The genome sequences presented here thus contribute towards a better understanding of both the pathogenicity and biotechnological potential of these species.